A new history of Japanese cinema : a century of narrative film - Standish, Isolde (New York, N.Y. ; London : Continuum, 2005)
In A New History of Japanese Cinema Isolde Standish focuses on the historical development of Japanese film. She details an industry and an art form shaped by the competing and merging forces of traditional culture and of economic and technological innovation. Adopting a thematic, exploratory approach, Standish links the concept of Japanese cinema as a system of communication with some of the central discourses of the twentieth century: modernism, nationalism, humanism, resistance, and gender.

After an introduction outlining the earliest years of cinema in Japan, Standish demonstrates cinema's symbolic position in Japanese society in the 1930s - as both a metaphor and a motor of modernity. Moving into the late thirties and early forties, Standish analyses cinema's relationship with the state-focusing in particular on the war and occupation periods. The book's coverage of the post-occupation period looks at "romance" films in particular. Avant-garde directors came to the fore during the 1960s and early seventies, and their work is discussed in depth. The book concludes with an investigation of genre and gender in mainstream films of recent years.

In grappling with Japanese film history and criticism, most western commentators have concentrated on offering interpretations of what have come to be considered "classic" films. A New History of Japanese Cinema takes a genuinely innovative approach to the subject, and should prove an essential resource for many years to come.
Filmografija: str. 365-386.
Bibliografija: str. 387-395.- Kazalo
Keywords: Motion pictures -- Japan -- History; film - Japan - povijest; japanski film